1997
DOI: 10.1111/j.1365-2621.1997.tb03991.x
|View full text |Cite
|
Sign up to set email alerts
|

Mackerel Cathepsins B and L Effects on Thermal Degradation of Surimi

Abstract: During surimi processing, cathepsins B and L activities in minced, leached and NaCl-ground meats were 6.02, 5.23, and 4.07 units/g, respectively. About 80% activity remained in surimi after 8 wk storage at Ϫ40ЊC suggesting that these proteinases were stable and difficult to remove. At 40Њϳ55ЊC, pH 6.5ϳ7.5, cathepsins B and L and purified cathepsin B had high hydrolytic activity on myosin heavy chain (MHC). The strength of surimi gel with cathepsins B and L or with purified B decreased (pϽ0.05) after 2 hr incub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 41 publications
6
43
0
3
Order By: Relevance
“…Proteolytic activity in muscles is high at temperatures above 508C and causes the rapid and severe degradation of myofibrillar proteins, particularly myosin (Wasson, Babbitt, & French, 1993). The results of the present study were similar to the work of Jiang, Lee, Tsao, & Lee (1997), who showed that cathepsins B and L or purified cathepsin B of mackerel muscle not only degraded MHC but also partially degraded actin in pH 6.5 or 7.0 after 5 h of incubation at 558C. Jiang et al (1996) indicated that actomyosin of mackerel surimi was incubated at 378C for 12 h; degradation of MHC at pH 6.0-7.5 might be due to the action of calpains.…”
Section: Degradation Of Bmpsupporting
confidence: 89%
“…Proteolytic activity in muscles is high at temperatures above 508C and causes the rapid and severe degradation of myofibrillar proteins, particularly myosin (Wasson, Babbitt, & French, 1993). The results of the present study were similar to the work of Jiang, Lee, Tsao, & Lee (1997), who showed that cathepsins B and L or purified cathepsin B of mackerel muscle not only degraded MHC but also partially degraded actin in pH 6.5 or 7.0 after 5 h of incubation at 558C. Jiang et al (1996) indicated that actomyosin of mackerel surimi was incubated at 378C for 12 h; degradation of MHC at pH 6.0-7.5 might be due to the action of calpains.…”
Section: Degradation Of Bmpsupporting
confidence: 89%
“…However, when stored for a longer time, the activities changed little. Jiang et al (1997) found that 82% of activities of purified cathepsin in mackerel remained even after 8 weeks when stored at pH 6.5, at À40°C. In our research, cathepsins were also found to be relatively stable for a week at low temperature (4°C) in acidic environment, especially cathepsin L.…”
Section: Proteolytic Activities During Fermentation and Storagementioning
confidence: 98%
“…This is in accordance with our results, showing a decline in collagenolytic activity and an increase in catheptic activities during fermentation. The activation of cathepsins by the decline in pH may be due to conversion from precursor or intermediate forms into mature form by acidification and leakage of lysosomal enzymes caused by rupture of membranes (Jiang, Lee, Tsao, & Lee, 1997;Liu, Yin, Zhang, Li, & Ma, 2006. The inactivation of collagenase was due to its instability under acidic conditions (Simpson, 2000).…”
Section: Proteolytic Activities During Fermentation and Storagementioning
confidence: 98%
“…Estudos feitos por Jiang et al (1997) com peixes (Scomber australasicus) preparados para surimi demonstram que as catepsinas B e L conservam 82% da sua atividade enzimática após congelamento, por oito semanas, a -40ºC. Pode-se, então, supor que, a conservação das proteínas miofibrilares das amostras é devida à liofilização e não ao congelamento.…”
Section: Eletroforese Em Sds-pageunclassified